HUBUNGAN PERILAKU OLAHRAGA TERHADAP HIPERTENSI PADA LANSIA DI PUSKESMAS SIDOMULYO PEKANBARU - Eko Kuswandono (Ensiklopedia of Journal, 2019)
Aging happens to seniors increased physiological changes impacting the disease appears and is often inflicted on elderly. At the ripe old age happen various setbacks on the organs of the body. So the elderly easy once stricken with a disease like hypertension. The purpose of this research is to identify the relationship of sport behavior to disease of hypertension in Elderly in Sidomulyo Soweto Clinics. This research uses the method crosectional. Sampling with a purposive sampling technique with a total of 86 respondents. The results of the research study shows that there is a relationship of sports behavior to disease of hypertension in elderly in Sidomulyo Soweto Clinics. (P-value 0.004), so that the behavior of the sport can continue to be used as special nursing interventions and community nursing.